Memory and plasticity impairment after binge drinking in adolescent rat hippocampus: GluN2A/GluN2B NMDA receptor subunits imbalance through HDAC2. (6th May 2019) - Drissi, Ichrak; Deschamps, Chloé; Fouquet, Grégory; Alary, Rachel; Peineau, Stéphane; Gosset, Philippe; Sueur, Harold; Marcq, Ingrid; Debuysscher, Véronique; Naassila, Mickael; Vilpoux, Catherine; Pierrefiche, Olivier
Abstract: Ethanol (EtOH) induces cognitive impairment through modulation of synaptic plasticity notably in the hippocampus. The cellular mechanism(s) of these EtOH effects may range from synaptic signaling modulation to alterations of the epigenome. Previously, we reported that two binge‐like exposures to EtOH (3 g/kg, ip, 9 h apart) in adolescent rats abolished long‐term synaptic depression (LTD) in hippocampus slices, induced learning deficits, and increased N ‐methyl‐d ‐aspartate (NMDA) receptor signaling through its GluN2B subunit after 48 hours. Here, we tested the hypothesis of EtOH‐induced epigenetic alterations leading to modulation of GluN2B and GluN2A NMDA receptor subunits. Forty‐two days old rats were treated with EtOH or the histone deacetylase inhibitor (HDACi) sodium butyrate (NaB, 600 mg/kg, ip) injected alone or 30 minutes before EtOH. After 48 hours, learning was tested with novel object recognition while synaptic plasticity and the role of GluN2A and GluN2B subunits in NMDA‐fEPSP were measured in CA1 field of hippocampus slices. LTD and memory were impaired 48 hours after EtOH and NMDA‐fEPSP analysis unraveled changes in the GluN2A/GluN2B balance. These results were associated with an increase in histone deacetylase (HDAC) activity and HDAC2 mRNA and protein while Ac‐H4K12 labelling was decreased. EtOH increases expression of HDAC2 and mRNA level for GluN2B subunit (but not GluN2A), while HDAC2 modulates the promoter of the gene encoding GluN2B. Interestingly, NaB pretreatment prevented all the cellular and memory‐impairing effects of EtOH. In conclusion, the memory‐impairing effects of two binge‐like EtOH exposure involve NMDA receptor‐dependent LTD deficits due to a GluN2A/GluN2B imbalance resulting from changes in GluN2B expression induced by HDAC2. Abstract : Immunolabelling for HDAC2 in hippocampusCA1 area of adolescent rats was increased 48h after two ethanol binge‐like exposure, an effect prevented by a pre‐treatment with NaB, an inhibitor of histone deacetylase (HDAC). This reveals the involvement of epigenetic in the effects of ethanol after only two exposure which may be link to ethanol‐induced cognitive deficits.